Implementation of the Principal's Democratic Leadership Style in the Independent Learning Curriculum - Nur Hidayah Br Karo; Elma Batasia Siregar; Freddy Giawa; Arif Rahman; Deny Setiawan (Didaktika: Jurnal Kependidikan, 2024)
The Merdeka Belajar curriculum is a new education policy in Indonesia that gives greater autonomy to schools. Its successful implementation depends on the leadership of the principal, in which the democratic leadership style is considered effective. This study aims to explore in depth the application of the principal's democratic leadership style in the implementation of the Merdeka Belajar Curriculum. Qualitative research with case studies at SMK Aviation PBD using interviews, observations, and documentation studies. Data analysis is carried out inductively by data reduction, data presentation, and conclusions. The results showed that school principals apply a democratic leadership style by involving stakeholders, giving teachers space to innovate, and facilitating collaboration between teachers. This creates a participatory and collaborative climate that supports curriculum implementation. However, challenges such as teacher resistance, lack of facilities, and lack of parental understanding were also found.